Using Alternative Transient Program and Electromagnetic Transients Programs (ATP/EMTP) in lightning overvoltages analysis - Mrvić, Jovan (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
The goal of this paper is to introduce a procedure for risk assessment of insulation failure due to storm surges. The simulations were carried out in ATP / EMTP software, which allowed the use of the Monte Carlo method for the statistical analysis of insulation coordination. The paper gives a detailed account of modelling of all the elements relevant to the analysis. At the same time, the capabilities of the programming language MODELS (allows the creation and implementation of new complex components within the ATP software) are discussed